Masa Kepemimpinan Raden Fatah 1478-1518 - Sari, Silvia Eka (Estoria: Journal of Social Science and Humanities, 2021)
Perkembangan Agama Islam di tanah Jawa tidak terlepas dari peranan para wali dan kesultanan-kesultanan Islam pada masa itu. Salah satu kesultanan yang berperan besar dalam penyebaran Agama Islam di Jawa adalah Kesultanan Demak. Kesultanan Demak adalah kesultanan pertama di Pulau Jawa yang sangat berpengaruh bukan hanya dalam menyebarkan agama Islam sampai ke daerah-daerah pedalaman, tetapi Demak juga menjadi tempat transitnya para pedagang Islam yang datang dari timur dan barat, di tangan Demak daerah-daerah yang sebelumya dibawah kekuasaan Hindu-Buddha ditaklukkan lalu di-Islamkan. Namun dibalik itu semua, terdapat seseorang yang sangat berperan besar yaitu Raden Fatah. Raden Fatah adalah pendiri sekaligus penguasa pertama Kesultanan Demak. Di tangan beliau Demak berdiri dan berkembang pesat menyaingi kerajaan-kerajaan lain pada masa itu. Berbagai macam cara diterapkan Raden Fatah untuk terus mengembangkan Demak. Selama 40 tahun beliau mengabdikan diri untuk Demak, lalu setelah beliau wafat perannya itu digantikan oleh anaknya.The development of Islam in Java was inseparable from the role of the Wali and Islamic Sultanates at that time. One of the sultanates that played a major role in the spread of Islam in Java was the Demak Sultanate. The sultanate of Demak was the first sultanate on the island of Java which was very influential not only in spreading Islam to the interior areas,but Demak was also a transit point for Islamic traders who came from east and west. It was in the hands of Demak that the areas that had previously been under Hindu-Buddhist rule were conquered and then converted to Islam. But behind all that, there is someone who plays a big role, namely Raden Fatah. Raden Fatah is the founder and first ruler of the Sultanate of Demak in his hands Demak stood and grew rapidly to rival other kingdoms at that time. Raden Fatah applied various kinds of efforts to continue to develop Demak. For 40 years, he devoted himself to Demak, then after he died his role was replaced by his son.